Integrated quantity and quality modeling and optimization of a manufacturing system under fractional inspection - Zhou, Xiaoyu (2014)
The independent research is focused on the analytical modeling of a Machine-Buffer-Inspection manufacturing system that incorporates fractional inspection plans. Multiple system parameters and performance measures are considered in the model together with appropriate assumptions made. A profit objective function is then developed to help investigate the financial performance and its sensitivity to system parameters, especially the ones related to fractional inspection plan.